Molcontroller: A VMD Graphical User Interface Featuring Molecule Manipulation - Wu, ChenChen; Liu, Shengtang; Zhang, Shitong; Yang, Zaixing (Journal of chemical information and modeling, 2020)
Visual Molecular Dynamics (VMD) is one of the most widely used molecular graphics software in the community of theoretical simulations. So far, however, it still lacks a graphical user interface (GUI) for molecular manipulations when doing some modeling tasks. For instance, translation or rotation of a selected molecule(s) or part(s) of a molecule currently only can be achieved using scripts. Here, we use the toolkit to develop a user-friendly GUI for VMD, named , which is featured by allowing users to quickly and conveniently perform various molecular manipulations. This GUI might be helpful for improving the modeling efficiency of VMD users.